The Financial Crisis and Its Impacts on Global Agriculture - Lin, Justin Yifu (2012)
The financial crisis arose in the industrial countries, but has affected developing countries through higher interest rates, sharp changes in commodity prices, and reductions in investment, trade, migration, and remittances. For most low-income countries, shocks that affect food prices or wage rates for unskilled workers seem likely to have the biggest impact on poverty, with the declines in key food prices associated with the crisis helping to reduce poverty. Policies to address the crisis must include measures to deal with: financial sector problems; the resulting reductions in aggregate demand; and the particular vulnerabilities of poor people.